Determination analysis of production cost calculation through the full costing method - Rotinsulu, Megantika J.; Lambey, Robert; D. Latjandu, Lady (Institute of Computer Science (IOCS), 2023)
Waani Furniture is a business that operates in the manufacturing sector, which produces various kinds of interiors, namely producing household furniture. This business has a problem in determining the production cost only using a simple method and not classified cost elements. This research aims to determine the calculation of the wardrobe production basic cost using the full costing calculation method. The research involved Waani Furniture located in Leilem Village, Sonder District, Minahasa as the research object. The method used to analyze this research is a qualitative approach of descriptive analysis with data collection through interviews, observation, and documentation. The results indicate that there is a significant difference in the production cost calculation because if the company uses the full costing method, the production cost is higher than the method determined by the company. The difference in cost price occurs due to different cost calculations as the company does not include all costs that should be used in determining the production cost. Therefore, companies need to classify cost components in the production cost. It is expected that companies can consider to calculate the production cost using the full costing method to produce more detailed and accurate data.